2022
DOI: 10.3390/vaccines10020144
|View full text |Cite
|
Sign up to set email alerts
|

microRNA, a Subtle Indicator of Human Cytomegalovirus against Host Immune Cells

Abstract: Human cytomegalovirus (HCMV) is a double-stranded DNA virus that belongs to the β-herpesvirus family and infects 40–90% of the adult population worldwide. HCMV infection is usually asymptomatic in healthy individuals but causes serious problems in immunocompromised people. We restricted this narrative review (PubMed, January 2022) to demonstrate the interaction and molecular mechanisms between the virus and host immune cells with a focus on HCMV-encoded miRNAs. We found a series of HCMV-encoded miRNAs (e.g., m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 132 publications
0
2
0
Order By: Relevance
“…In our study, all PSS patients who underwent glaucoma surgery developed iris depigmentation. Kam et al [ 2 ] identified iris depigmentation as a clinical biomarker for predicting chronic or recurrent anterior uveitis CMV infection in a prospective cohort study [ 6 ]. Our findings are consistent with theirs, revealing that PSS patients with glaucomatous damage not only had iris depigmentation but also increased CMV DNA copy numbers in aqueous humor compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, all PSS patients who underwent glaucoma surgery developed iris depigmentation. Kam et al [ 2 ] identified iris depigmentation as a clinical biomarker for predicting chronic or recurrent anterior uveitis CMV infection in a prospective cohort study [ 6 ]. Our findings are consistent with theirs, revealing that PSS patients with glaucomatous damage not only had iris depigmentation but also increased CMV DNA copy numbers in aqueous humor compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic criteria for PSS were as follows [1]: (1) recurrent intermittent, acute, mild non-granulomatous anterior uveitis; (2) IOP higher than 21 mm Hg; (3) keratic precipitates on corneal endothelial surface; (4) cell and flare in the anterior chamber; (5) open anterior chamber angle; and (6) no iris posterior synechiae or posterior inflammation. Secondary glaucoma development in PSS patients was defined by the following criteria: (1) persistent elevation of IOP in the affected eye (>21 mm Hg), with a bilateral IOP difference of >8 mm Hg; and (2) glaucomatous cupping and retinal nerve fiber layer (RNFL) loss accompanied by progressive visual field defects [6][7][8].…”
Section: Patientsmentioning
confidence: 99%